Development of motivation for the achievements of schoolchildren under the conditions of the updated learning content - Абилдаева, Гульназ (Pedagogy and Psychology, 2023)
The scientific article presents the results of a study of the achievement motivation of schoolchildren during the transformation of school education. The purpose of the study is to conduct a comparative analysis to study the achievement motivation of students in the control and experimental groups. The experimental results obtained confirm that the updated educational trajectory of students' learning will be assimilated effectively, provided that psychological and pedagogical conditions are created for the formation and development of achievement motivation in middle school students. Research methods: Personal questionnaire "Big Five - BigFive"; methodology “Studying the need for achievement” by Yu. M. Orlov; “Achievement Motivation Measurement Test Questionnaire” by A. Mekhrabian; “Diagnosis of the motivational structure of personality” Milman. The results obtained indicate the need to create psychological and pedagogical conditions that contribute to the formation and development of achievement motivation during the period of study in a modern school. The development of motivation to achieve success activates the desire for self-development and increases confidence in achieving the goal.